A comparison of toxicity and health care resource use between eribulin, capecitabine, gemcitabine, and vinorelbine in patients with metastatic breast cancer treated in a community oncology setting. (June 2015) - Dranitsaris, G; Beegle, N; Kalberer, T; Blau, S; Cox, D; Faria, C
Background: Capecitabine (C), gemcitabine (G), and vinorelbine (V) are commonly used as single agents in patients with metastatic breast cancer. Eribulin (E) is one of the most recent cytotoxic agents to gain regulatory approval for metastatic breast cancer in the United States as a single agent. EMBRACE – a large randomized trial demonstrated the safety and overall survival benefit of eribulin in heavily pretreated metastatic breast cancer patients compared to treatment of physician's choice. In this analysis, toxicity and the associated health care resource use were compared between the four agents in a sample of metastatic breast cancer patients treated in a US community oncology setting. Methods: This study identified 411 patients (C=144, G=81, V=96, and E=90) who were treated in 19 community oncology clinics over the preceding two-year period. Data collection included baseline patient and disease characteristics, duration of therapy, use of supportive care drugs, type of dose limiting toxicities, and their impact on overall health care resource use. Results: The median lines of therapy for C, G, V, and E were second, third, third, and fourth, respectively. Patients were comparable with respect to baseline comorbidities, performance status, serum creatinine, hemoglobin, neutrophil, and platelet counts. The proportion reporting at least one adverse event (any grade) with C, G, V, and E was 45%, 65%, 75%, and 63%. The most commonly reported toxicities (regardless of grade) for C, G, and V were diarrhea (19.4%), anemia (34.6%), and neutropenia (50.0%), respectively. The most common toxicity for E was neutropenia (32.2%). Overall, 5.6%, 19.8%, 22.9%, and 22.2% of patients receiving C, G, V, and E required at least one medical intervention to manage a toxic event. Toxicity was the cause of treatment discontinuation in 25.7%, 8.6%, 11.5%, and 8.9% of C, G, V, and E patients, respectively. The primary cause for treatment discontinuation in all four cohorts was disease progression. Conclusions: Eribulin demonstrated a comparable patient safety profile to gemcitabine and vinorelbine, even when administered after three lines of prior therapies. Capecitabine was generally used in earlier lines, had less neutropenia and anemia, but more treatment discontinuations due to toxicity.